Disclosure of Biology Teacher Technological Pedagogical Content Knowledge as an Indicator of Learning Quality in Jember, Indonesia - Ali Usman*; Novy Eurika; Ika Priantari (Universitas Syiah Kuala, 2023)
Understanding the quality of biology learning implemented by teachers in Jember is essential to pay attention to. This study aims to identify biology teachers' technological pedagogical content knowledge (TPACK) ability profiles. The research method combines quantitative and qualitative approaches with an explanatory sequential design. At the quantitative research stage, the questionnaire method was used as the main instrument, which was then strengthened with a qualitative approach through interviews and documentation studies. Data collection was carried out through surveys and interviews. The population of this study were biology teachers in Jember, Indonesia, with a total sample of 33 biology education teachers. The survey instrument used is based on previous research conducted by Muhaimin, with a standard validity coefficient of 0.71-0.93. The survey questionnaire was distributed using google forms, with the assistance of two high school teachers and two research assistants. The results showed that the TPACK ability of high school biology teachers in Jember was still low due to a lack of access to information about technological developments and new learning media. Information about technological developments and new learning media is only obtained from university students participating in the field experience program. Therefore, teachers must be encouraged to improve their TPACK skills to provide a more effective learning process